CRISPR-Cas9 System for Agriculture Crop Improvemen - Sharma, A.; Badola, P. K.; Trivedi, P. K.
Genome editing technologies have shown their enormous potential in development of improved crop varieties with key agronomic traits and have also contributed as a valuable research tool to allow more rapid analysis of desired genes responsible for growth and development, biofortification, disease resistance and improved tolerance toward numerous biotic and abiotic stresses. Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)represents a breakthrough technology available to overcome major obstacles and challenges in crop production. CRISPR has emerged to be the widely employed and popular technology of the twenty-first century. Owing to its precision and silencing multiple genes simultaneously, researchers worldwide now employ this technology for improving crop yield and quality and allowing characterization of desired gene families. In recent years, CRISPR-based technologies have been widely used to systematically increase or decrease the activity of individual genes in a way that they can be precisely deleted, modified and replaced. One of the major concerns regarding the presence of foreign DNA in GM crops can be addressed well with the use of precise genome-editing tools. The use of CRISPR has revolutionized genome engineering technology and set new standards both in basic biological research as well as applied fields such as agriculture research.